2022
DOI: 10.5897/jat2021.0501
|View full text |Cite
|
Sign up to set email alerts
|

The nexus between bank size and financial performance: Does internal control adequacy matter?

Abstract: The economic development of any nation is largely dependent on the stability of the nation's banking industry, because the industry promotes the savings culture of the public, aids capital funding, implements the monetary policy of a country and promotes the facilitation of international trade. Therefore this study examined the effect of bank size on the financial performance of listed Deposit Money Banks in Nigeria (DMBN). Also, the study examined the moderating effect of internal control adequacy on the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Bank size is one of the vital determinants of a bank's financial performance and it can be measured in terms of the value of total assets, customer deposits, and number of employees (Akinola, 2022). Examining how the treasury single account (TSA) policy impacted the Tanzanian banking sector's performance in relation to ownership concentration, bank size, and macroeconomic variables, Mkaro et al (2023) found that while foreign and state-owned banks were more resilient, private and domestic banks' performance deteriorated after TSA adoption.…”
Section: Bank Size and Roamentioning
confidence: 99%
“…Bank size is one of the vital determinants of a bank's financial performance and it can be measured in terms of the value of total assets, customer deposits, and number of employees (Akinola, 2022). Examining how the treasury single account (TSA) policy impacted the Tanzanian banking sector's performance in relation to ownership concentration, bank size, and macroeconomic variables, Mkaro et al (2023) found that while foreign and state-owned banks were more resilient, private and domestic banks' performance deteriorated after TSA adoption.…”
Section: Bank Size and Roamentioning
confidence: 99%
“…Thus, more prudent and stricter corporate governance practices are to be ensured to guide against opportunistic inclinations and rent‐seeking in the operations of banks. Banks play fundamental roles in mobilizing and channeling funds to drive entrepreneurial and developmental agendas as well as providing financial services that spur and expansion of economic activity (Abisola, 2022; Akinola, 2022; Belasri et al, 2020; Gržeta et al, 2023; Haider & Mohammad, 2022; Husnain et al, 2021; Khalil, 2022; Lotto, 2019; Ojeyinka & Akinlo, 2021; Olaniyi et al, 2023; Sulaeman et al, 2022). This is a pointer to the fact that all other sectors of the economy depend on the viability and stability of the banking system (Sallemi et al, 2022).…”
Section: Background To the Studymentioning
confidence: 99%
“…Using new technology has led to many changes and developments, including the adoption of total quality management and a just-in-time procurement system, as well as the rise of today's highly competitive business environment. These changes have led to a need for better performance measures to sustain a continuous improvement process in a competitive environment with low profit margins (Akinola, 2022;Aliyu, Abdullahi, & Bakare, 2020;Ogbebor, Osho, & Oguntodu, 2020). Additionally, the increasing demand and exploration for the utilisation of non-performance measures such as quality and customer satisfaction have necessitated that both financial and non-financial performance measures are considered in the totality of measuring corporate performance (Owolabi & Adeosun, 2021;Owolabi, Adetula, & Taleatu, 2016).…”
Section: Literature Review Conceptual Reviewmentioning
confidence: 99%